DETERMINATION OF CONSUMER VALUE AND PURCHASE DECISIONS: ANALYSIS OF PRODUCT QUALITY, LOCATION, AND PROMOTION - Septiano, Renil; Sari, Laynita (Dinasti International Journal of Digital Business Management, 2021)
Literature review is useful as a first step to initiating a study. Before determining the title, it's a good idea to prepare supporting articles for research, including previous research or as relevant research. Relevant and theory-reinforced articles are needed to look at the relationship between variables and build hypotheses. This article discusses variables that affect consumer value and consumer decisions to make decisions. The variables of product quality, location and promotion became the variables with the 3 highest values ??at the time of the pre-research survey. Of course not all factors that influence purchasing decisions and consumer value are discussed in this article, only a small part will be reviewed and reviewed. The results of the review show that all exogenous variables have a direct or indirect effect on endogenous variables.